A novel method to precisely quantify hepatitis B virus covalently closed circular (ccc)DNA formation and maintenance - Tu, Thomas; Zehnder, Benno; Qu, Bingqian; Ni, Yi; Main, Nathan; Allweiss, Lena; Dandri-Petersen, Maura; Shackel, Nicholas; George, Jacob; Urban, Stephan (Antiviral research, 2020)
Hepatitis B virus (HBV) is the major cause of virus-associated liver disease. Persistent HBV infection is maintained by its episomal genome (covalently closed circular DNA, cccDNA), which acts as a template for viral transcripts. The formation of cccDNA is poorly characterised due to limited ability to quantify it accurately in the presence of replicative intermediates. Here, we describe a novel cccDNA quantification assay (cccDNA inversion quantitative PCR, cinqPCR), which uses restriction enzymes to invert a DNA sequence close to the gap region of Genotype D HBV strains, including the isolate widely used in experimental studies. Importantly, cinqPCR allows simultaneous normalisation to cellular DNA in a single reaction, provides absolute copy numbers without requiring a standard curve, and has high precision, sensitivity, and specificity for cccDNA compared to previous assays. We first established that cinqPCR gives values consistent with classical approaches in both in vitro and in vivo (humanised mice) HBV infections. We then used cinqPCR to find that cccDNA is formed within 12 h post-inoculation (hpi). cccDNA formation slowed by 28 hpi despite de novo synthesis of HBV DNA, indicating inefficient conversion of new viral genomes to cccDNA within infected cells. Finally, we show that cinqPCR can be used as a 96-well screening assay. Thus, we have developed an ideal method for testing current and future anti-cccDNA therapeutics with high precision and sensitivity.
Gesehen am 22.12.2025